Work-life balance: the relationship with informal organizational support and turnover intention / Khairuddin Naim Mohd Zain - Khairuddin Naim , Mohd Zain (2018)
Due to the changes in the demographic pattern where employees tend to delay their marriage, there appears to be an increase in proportion of single or never married employees in the global workforce. However, both married and single employees are still treated in the same manner with regards to Work-Life balance. Traditionally, the word ‘life’ has been referred to as ‘family’ which has been defined in a narrow sense of employees who are parents with children. This concept may no longer apply to all employees especially single employees with no family obligations. In view of the impending difference on how “Life” is viewed by different group of employees, this study intends to test the influence of two different form of informal support; Informal personal support and informal family support on the perception of balance among these two groups of employees. After the preliminary analysis, the informal support variables had to be change to informal supervisor support and informal career support. The study set out to test is respondents from different groups perceived the two forms of informal support differently and whether the influence of these variables in turnover intention were mediated by Work-Life or Work-Family balance. Data was gathered from 446 private sector employees. The result shows that both informal supports positively influence Work-Family Balance (WFB) and Work-Life Balance (WLB). The result also shows that WFB and WLB mediate the relationship between Informal Supervisor Support (ISS) and Turnover Intention (TOI) as well as between Informal Career Support (ICS) and TOI. However, the result shows that marital status does not moderate the relationship between WFB and TOI as well as between WLB and TOI. Thus, marital status does not significantly influence the strength of WFB / WLB and TOI. The implications of this study spread into the scholars and practitioners as it would strengthen the knowledge about WFB and WLB and suggest a practical application pertaining WLB for organizations to gain the competitive advantage. The results suggest that the supports are needed in two separate variables known as ISS and ICS, adding new knowledge to the scholars. As per the practitioners, they should pay attention to the future changes of need of their employees who are married as well as the need of their employees who are single.